(untitled) (Global Journal of Human-Social Science, 2025)
The objective of this article is to discuss the teaching of Deaf Literature as an important cultural production of the Deaf Community and to identify its formative and identity-building role Furthermore it proposes a reflection on the place of this so-called marginal literature in the official literary canon As theoretical support important studies proposed by Candido 2011 Carvalho 2019 Peters 2002 Karnopp 2006 among others were used